An experimental investigation into the effect two-phase flow induced vibrations have on a J-shaped flexible pipe - Pickles, David J.; Hunt, Graeme; Elliot, Alexander J.; Cammarano, Andrea; Falcone, Gioia (Elsevier, 2024)
Multiphase flow inside of pipes occurs in a wide variety of engineering applications, including offshore deep-water oil and gas transport. Vibrations induced by the flow inside of the pipe can lead to its mechanical failure and thus lead to uncontrolled release of the fluids being transported. In subsea applications, flexible J-risers are often employed to deliver the produced fluids from the seafloor to the host platform. Despite the potentially significant liabilities associated with subsea hydrocarbon leaks, there has been a distinct lack of investigations into how flow induced vibrations in large scale, pressurised flexible J-risers can lead to system integrity loss. Previous investigations have generally focused on the response of rigid pipes or small scale, unpressurised flexible risers. This study presents an investigation into the response of a 10 m long, 50.8 mm internal diameter composite riser containing a tensile armour helical structure to a variety of two-phase, water-nitrogen flows at 10.8 barg of pressure and ambient temperature. High speed cameras were used to investigate the structure of the flow at either end of the flexible riser, whilst synchronised surface mounted strain gauges and accelerometers were used to investigate the response of the pipe. Time-averaged data were acquired to assess the general response of the pipe, whilst a statistical analysis of the fluctuations highlighted the movement of the pipe. One-dimensional and computational fluid dynamics simulations were used to define the experimental test matrix and provide further insight into the structure of the flow inside the J-riser. Single-phase gas flow was found not to cause the J-riser to move significantly, whilst multiphase flow led to significant in-plane movement of the pipe. Increasing the liquid flow rate (or decreasing the gas flow rate) increased the mean strain experienced by the pipe. At low gas flow rates, the pipe oscillated smoothly about its mean position, but at higher gas flow rates a violent intermittent whipping motion was observed. The latter produced large in-plane and out-of-plane movement of the pipe which could pose a threat to system integrity. This work offers new insights into fluid-structure interactions in large scale engineering applications, contributing to improved system design and control.
Keywords: Fluid-structure interaction; Slug flow; Experiment; Multiphase flow; Flow Induced vibration